1979
DOI: 10.1007/bf00894385
|View full text |Cite
|
Sign up to set email alerts
|

Some effects of positive life events on community mental health

Abstract: Measures of positive and negative events were derived from a life-event inventory to test the predictions of an equilibrium model and a positive mental health model of psychological well-being. These measures were related to indicators of individual and community well-being with data obtained through a household survey of 454 residents. Residents who reported more negative events also reported more psychological distress and less positive adjustment. Positive events were associated with reports of positive adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
0
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 17 publications
2
32
0
1
Order By: Relevance
“…The data from Reker and Wong (1983) are consistent with the general notion that optimism confers benefits on physical well-being We interpret the findings cautiously, however, for two reasons First, the prospective correlations between optimism and physical health were not adjusted for any association that might have existed between optimism and the cntenon vanables at the outset of the study Second, Reker and Wong used a procedure to measure optimism that was considerably removed from a measure of generalized outcome expectancies These lnterpretational cautions are less problematic, however, when viewed in conjunction with a study that we conducted ourselves (Scheier & Carver, 1985, Study 3) Although we were unaware of the Reker and Wong study while our own study was planned and conducted, our findmgs mesh nicely with theu-s Our pnmary purpose was to begin to explore the impact of dispositional optimism on processes underlymg coping with stress in a health-relevant context To do this, we tracted the coping success of a group of college students who were in a penod of time that is ordmanly very stressful for them the final four weeks of an academic semester of study We assumed that most students dunng this penod would encounter a number of problems m self-management, as they attempted to juggle their schedules so as to meet the vanous studygoals that they had set for themselves and get their work done on time Our reasoning with respect to the effects of optimism presumed that when persons are confronted with impediments to goal-attainment during the course of their daily lives, they pause from their goal-directed efforts (if only momentanly) and attempt to decide whether or not future efforts will be futile-a sequence which we have previously labeled "interruption and expectancy assessment " If optimism is a generalized expectancy for favorable outcomes, then optimism should instill a sense of confidence m dealing with whatever obstacles are encountered Assuming that the problems are capable of solution, the positive expectancies held by optimistic persons-and the continued efforts to which the expectancies give nse-should cause them to deal with the problems more effectively than those less optimistic in onentation Thus, obstacles that anse dunng the course of day-to-day self-regulatory activities should be less disruptive and have less adverse consequences for optimists than pessimists (cf Reich & Zautra, 1981, Zautra & Simons, 1979 In the study we conducted, success at coping was assessed by measunng the extent to which subjects reported being bothered by physical symptoms Subjects completed the LOT and a physical symptom checklist twice-at the outset of the study and four weeks later (on the last day of classes) The symptom checklist asked participants to mdicate the extent to which they had been bothered by each of 39 different physical symptoms dunng the preceding two-week penod Most of the symptoms on the checklist were relatively mild and included effects that students might reasonably be expected to expenence-for example, coughs, fatigue, muscle soreness, and dizziness (see Cohen & Hoberman, 1983, for detail) The major findmgs of the study are presented m Figure 1 Optimism was negatively associated with symptom reporting at both assessment penods, as expected More importantly, optimism and symptom reporting were also negatively correlated across time That is, persons who reported being optimistic at the start of the study were the ones who reported fewer symptoms four weeks later Indeed, the prospective relationship betwen optimism and symptom rep...…”
Section: Measuring Dispositional Optimism the Life Orientation Testmentioning
confidence: 98%
“…The data from Reker and Wong (1983) are consistent with the general notion that optimism confers benefits on physical well-being We interpret the findings cautiously, however, for two reasons First, the prospective correlations between optimism and physical health were not adjusted for any association that might have existed between optimism and the cntenon vanables at the outset of the study Second, Reker and Wong used a procedure to measure optimism that was considerably removed from a measure of generalized outcome expectancies These lnterpretational cautions are less problematic, however, when viewed in conjunction with a study that we conducted ourselves (Scheier & Carver, 1985, Study 3) Although we were unaware of the Reker and Wong study while our own study was planned and conducted, our findmgs mesh nicely with theu-s Our pnmary purpose was to begin to explore the impact of dispositional optimism on processes underlymg coping with stress in a health-relevant context To do this, we tracted the coping success of a group of college students who were in a penod of time that is ordmanly very stressful for them the final four weeks of an academic semester of study We assumed that most students dunng this penod would encounter a number of problems m self-management, as they attempted to juggle their schedules so as to meet the vanous studygoals that they had set for themselves and get their work done on time Our reasoning with respect to the effects of optimism presumed that when persons are confronted with impediments to goal-attainment during the course of their daily lives, they pause from their goal-directed efforts (if only momentanly) and attempt to decide whether or not future efforts will be futile-a sequence which we have previously labeled "interruption and expectancy assessment " If optimism is a generalized expectancy for favorable outcomes, then optimism should instill a sense of confidence m dealing with whatever obstacles are encountered Assuming that the problems are capable of solution, the positive expectancies held by optimistic persons-and the continued efforts to which the expectancies give nse-should cause them to deal with the problems more effectively than those less optimistic in onentation Thus, obstacles that anse dunng the course of day-to-day self-regulatory activities should be less disruptive and have less adverse consequences for optimists than pessimists (cf Reich & Zautra, 1981, Zautra & Simons, 1979 In the study we conducted, success at coping was assessed by measunng the extent to which subjects reported being bothered by physical symptoms Subjects completed the LOT and a physical symptom checklist twice-at the outset of the study and four weeks later (on the last day of classes) The symptom checklist asked participants to mdicate the extent to which they had been bothered by each of 39 different physical symptoms dunng the preceding two-week penod Most of the symptoms on the checklist were relatively mild and included effects that students might reasonably be expected to expenence-for example, coughs, fatigue, muscle soreness, and dizziness (see Cohen & Hoberman, 1983, for detail) The major findmgs of the study are presented m Figure 1 Optimism was negatively associated with symptom reporting at both assessment penods, as expected More importantly, optimism and symptom reporting were also negatively correlated across time That is, persons who reported being optimistic at the start of the study were the ones who reported fewer symptoms four weeks later Indeed, the prospective relationship betwen optimism and symptom rep...…”
Section: Measuring Dispositional Optimism the Life Orientation Testmentioning
confidence: 98%
“…When positive and negative moods are assessed separately, however, they are differentially related to pleasant and unpleasant events (Headey, Holmstrom, & Wearing, 1984;Stone, 1981;Warr, Barter, & Brownbridge, 1983;Zautra, 1983;Zautra& Reich, 1983;Zautra& Simons, 1979 (Beiser, 1974;Bradburn, 1969;Costa & McCrae, 1980, 1985aDiener, Larsen, & Emmons, 1984;Emmons & Diener, 1985;Lawton, 1984;Moriwaki, 1974;Phillips, 1967;Tellegen, 1982Tellegen, , 1985Warr et al, 1983;Zautra & Simons, 1979). '…”
mentioning
confidence: 99%
“…The "Separate Domain" Model The issues noted above are most explicitly addressed by Zautra and his colleagues (Block & Zautra, 1981;Zautra & Reich, 1983; Zautra and Simons, 1979), who have proposed that life events are related to well-being and to perceptions of life quality in two relatively independent domains: Positive life events promote positive affect, and negative life events promote negative affect. Zautra and Reich (1983) reviewed 17 studies in which the impact of positive and negative life events on negative affect was assessed.…”
mentioning
confidence: 99%